Rough \(Δ^m\)-Statistical Convergence of order \(α\) of Generalized Difference Sequences in Intuitionistic Fuzzy Normed Spaces - Kaur, Gursimran; Chawla, Meenakshi (Communications in Mathematics and Applications, 2025)
The prime direction of this research article is to explicate the perception of rough \(Δ^m\)-statistical convergence of order \(α\) of generalized difference sequences in intuitionistic fuzzy normed spaces. We showed certain rough convergence features, which give some new functional tools in the face of uncertainty, such as intuitionistic fuzzy normed spaces. We demonstrated some basic properties and examples which generates the results that this perception is more generic. Further, we added the set of \(Δ^m\)-statistical limit points and set of \(Δ^m\)-statistical cluster points and their relationship of rough \(Δ^m\)-statistically convergence of generalized difference sequences in these spaces.
Keywords: Intuitionistic normed spaces; Statistical convergence; Rough statistical convergence; Difference sequence; Generalized difference sequence